Social Justice in the Countries of Central and Eastern Europe - Skorupińska-Cieślak, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2025)
The article aims to compare the level of social justice in the countries of Central and Eastern Europe (CEE) in terms of the individual indicators that constitute the Social Justice Index and to determine their level of convergence with the European Union average. The paper also describes changes in this area of social justice in recent years and examines the relationship between social justice and industrial democracy. The analysis was based on statistical data from Eurostat and the results of a study conducted by the European Foundation for the Improvement of Living and Working Conditions, the European Institute for Gender Equality, and the Legatum Institute. The findings show that Romania achieves the worst results in most indicators in the Social Justice Index, but many of them have improved significantly in recent years. Slovenia, Czechia and Slovakia are the most successful in preventing poverty and equalising income. The degree of gender equality in all CEE countries was lower than the EU27 average. Finally, CEE countries that promote social dialogue and employee participation rights also have higher levels of social justice.